PENGARUH PEMBAKARAN BERULANG PADA LAHAN GAMBUT TERHADAP BEBERAPA KARAKTERISTIK TANAH DI DESA RASAU JAYA UMUM KABUPATEN KUBU RAYA KALIMANTAN BARAT - Astuti, Yuliana; Astiani, Dwi; Herawatiningsih, Ratna (Universitas Tanjungpura, 2020)
The National Disaster Management Agency (BNPB) identifies eight provinces considered prone to forest and land fires in Indonesia. Four provinces are in Sumatra and four are in Kalimantan, one of which is West Kalimantan. Forest and land fires seem to have become a disaster in West Kalimantan, especially every dry season. Burning activies in the preparation of land for agriculture in the village of Rasau Jaya General is still using a relatively simple technology, namely the method of